2009
DOI: 10.1007/s10661-009-0780-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particulate matter, atmospheric gases, temperature, and humidity on respiratory and circulatory diseases’ trends in Lisbon, Portugal

Abstract: This study addresses the significant effects of both well-known contaminants (particles, gases) and less-studied variables (temperature, humidity) on serious, if relatively common, respiratory and circulatory diseases. The area of study is Lisbon, Portugal, and time series of health outcome (daily admissions in 12 hospitals) and environmental data (daily averages of air temperature, relative humidity, PM 10 , SO 2 , NO, NO 2 , CO, and O 3 ) have been gathered for 1999-2004 to ascertain (1) whether concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 23 publications
2
22
0
1
Order By: Relevance
“…Positive relationship between SO 2 and PM10 was shown by İçağa and Sabah (2009). Distinctly negative correlations of SO 2 concentrations, but also those of PM10, with relative humidity, were demonstrated by Freitas et al (2010), Pires et al (2008), Czarnecka and Nidzgorska-Lencewicz (2011), and sulfur dioxide concentrations alone in the winter months, from December to February, were shown by Cuhudaroglu and Demirci (1997). On the other hand, the results reported by Elminir (2005) for Egypt indicate significantly higher annual average concentrations of both pollutants (particulate matter even twice) under high, more than 80 % relative humidity.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Positive relationship between SO 2 and PM10 was shown by İçağa and Sabah (2009). Distinctly negative correlations of SO 2 concentrations, but also those of PM10, with relative humidity, were demonstrated by Freitas et al (2010), Pires et al (2008), Czarnecka and Nidzgorska-Lencewicz (2011), and sulfur dioxide concentrations alone in the winter months, from December to February, were shown by Cuhudaroglu and Demirci (1997). On the other hand, the results reported by Elminir (2005) for Egypt indicate significantly higher annual average concentrations of both pollutants (particulate matter even twice) under high, more than 80 % relative humidity.…”
Section: Introductionmentioning
confidence: 87%
“…The noxious effects of particulate matter on the human body represent a well-studied area. Numerous published research reports declare that the concentration level of this pollutant is well correlated with morbidity that requires hospital care and even mortality caused by escalation of respiratory and circulation system disorders (Brunekreef and Holgate 2002;Dominici et al 2006;Freitas et al 2010;Kappos et al 2004;Lazaridis 2011;Medina et al 2004;WHO 2005). According to the assessment by Tainio et al (2010), the anthropogenic emission of primary fine particulate matter PM 2.5 in Europe causes a few thousand premature deaths a year in Poland.…”
Section: Introductionmentioning
confidence: 99%
“…CO has been associated with respiratory hospital admissions in several studies. [60] did not find any statistically significant relationship between respiratory hospital admissions and CO, while [49,[61][62][63][64] confirmed the positive role of CO on respiratory health effects. The impact of a long-lasting but low level exposure to CO on respiratory system is therefore still unclear.…”
Section: Season Ofmentioning
confidence: 98%
“…In contrast, [49] found that elevated PM 10 levels indicate a dominant role among the main air pollutants. [30,61] found that the association between particulate matter and health conditions was not significant, while others [38,60,64,[66][67][68][69][70][71] found that the number of admissions for respiratory causes rose significantly with increased exposure to particulate matter. It should be added that the health impact of particulates is complex as their biological effect can be influenced by the particle size and composition [30].…”
Section: Season Ofmentioning
confidence: 99%
See 1 more Smart Citation